2013
DOI: 10.3177/jnsv.59.232
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethyl Pyruvate Supplementation on Rat Fatty Liver Induced by a High-Fat Diet

Abstract: Continuous positive energy imbalance leads to obesity, which increases the risk of developing non-alcoholic fatty liver disease. The hepatoprotective effect of ethyl pyruvate has been revealed in several studies. Therefore, we examined the effect of ethyl pyruvate supplementation on liver cell damage, metabolism, membrane fluidity, and oxidative stress markers in rats fed a high-fat diet. After 6-wk feeding of a control or high-fat diet, Wistar rats were divided into 4 groups: control diet, control diet and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In the study reporting an increase of mitochondrial content after long-term HFD, the treatment was initiated at the age of 14 weeks, when the weight of the male Wistar rats was 366 ± 16 g [32]. Consistently, in our study the control rats at the age of 14 weeks were 365 ± 11 g [28], Modification in muscle metabolism may also be influenced by the duration of HFD. The chronological changes in the muscles of rats fed by HFD has been described in the study by Chanseaume et al [6].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the study reporting an increase of mitochondrial content after long-term HFD, the treatment was initiated at the age of 14 weeks, when the weight of the male Wistar rats was 366 ± 16 g [32]. Consistently, in our study the control rats at the age of 14 weeks were 365 ± 11 g [28], Modification in muscle metabolism may also be influenced by the duration of HFD. The chronological changes in the muscles of rats fed by HFD has been described in the study by Chanseaume et al [6].…”
Section: Discussionsupporting
confidence: 84%
“…Animals had free access to food and water and were kept at room temperature with a light-dark cycle of 12 h. After 6 weeks, both groups were subdivided into 4 groups: control diet (CC; n = 8), control diet and EtP (CP; n = 8), HFD (DC; n = 8), HFD and EtP (DP; n = 8). EtP was administered as 0.3% EtP solution in drinking water for the following 6 weeks [28]. At the end of 12th week, the rats were sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…EP had received interest as its hepatoprotective effects in fatty liver, hepatic ischemia-reperfusion injury, and acuteon-chronic liver failure [20]. EP downregulated the expression of multiple proinflammatory proteins, including IL-1β, TNF-α, and HMGB1 in animal experiments of endotoxemia and sepsis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that reduction in liver weight correlates with anti-obesity potential. 22 In few studies, instead of liver weight, the more sensitive % liver weight reduction parameter was used. We did not find reduction in % liver weight as HFD is not a good model to induce changes in liver and the effect of the extract on liver metabolism is negligible.…”
Section: Discussionmentioning
confidence: 99%